National Geographic Magazine [computer file] The 1930s (vol. LVIII, no. 1) Jan. 1930-April 1933, May 1933-August 1936, September 1936-December 1939 (Washington, DC National Geographic Society, 1888)
Rise to record heights in the stratosphere-nearly 14 miles above the earth-in the balloon Explorer II. Plunge half a mile under the sea with William Beebe in his bathysphere. Fly solo to Hawaii with the legendary Amelia Earhart in 1935. Ride along on the first motorized trips through the Himalayas and the first Trans-African motorcycle expedition. And experience many more captivating moments from the 1930s.
National Geographic: The 1930s provides a glimpse of a world in transition on easy-to-access CD-ROMs.
Twenty-four pages of illustrations in full color, Norway, a land of Stern Reality, Fjord and Fjells of Viking Land, North America's Oldest Metropolis, Adventures in color on Mexico's West Coast, To-day on "The Yukon Trail of 1898".
The complete National Geographic on CD-ROM was produced from archive of magazines collected in a central repository and is not representative of any single regional edition of National Geographic magazine.
Minimum requirements for Windows: Pentium 90MHz or faster, 24MB RAM, 70MB free hard-disk space, SVGA video card supporting 16-bit color, 16-bit sound card and speakers, 4x CD-ROM drive
Minimum requirements for Macintosh: PowerPC or higher, System 7.5 or higher, 32MB RAM, 70MB free hard-disk space, 640x840 16-bit color monitor, 4x CD-ROM drive.
Keywords: Explorer II; Himalayas; Motorcycle Expedition